Use of crops and livestock futures contracts in portfolios: an analysis of feasibility - Fabio L. Mattos; Joaquim Bento de Souza Ferreira Filho (Revista de Economia e Sociologia Rural, 2003)
According to Portfolio Theory, by combining assets that show a correlation inferior to one (1) among their individual returns, it becomes possible to create portfolios that reduce risk without damaging expected return. Crop and livestock futures contracts and company stocks show such a characteristic, which signals potential benefits when forming portfolios combining these two types of assets. This investment strategy is not often utilized in Brazil. The purpose of our research was to assess whether such an asset combination is actually advantageous to those creating investment portfolios in the Brazilian market. Our evaluation used instruments of analysis developed by Markowitz in Portfolio Theory and data about the return from crop and livestock futures contracts and stocks. The data was gathered from the Brazilian Futures and Commodities Exchange (BM&F) and Brazil’s National Association of Open Market Institutions (ANDIMA) between July 1994 and December 1998. The results of this work showed that the combination of these two types of assets in investment portfolios can be an interesting portfolio management alternative.